Composition, structure, and wear resistance of surface nanostructures obtained by electric spark alloying of 65G steel [Articol] - Yurchenco, E.; Ghilețchii, Gheorghe; Vatavu, Sergiu; Petrenco, Vladimir; Harea, Diana; Bubulincă, C.; Dikusar, Alexandr (My University, 2024)
A combination of X-ray diffraction and X-ray fluorescence analysis has shown that the strength- ened layer formed during electric spark alloying of 65G steel with a processing electrode made of the T15K6 hard alloy is a nanocrystalline material, the ratio of the crystalline and amorphous phases in which is achieved by changing the discharge energy. Since an increase in discharge energy leads to an increase in surface rough- ness and its amorphization, there is an optimal value of discharge energy at which maximum wear resistance of the resulting nanocomposites is achieved. At E = 0.2 J, the wear resistance of the hardened layer is 7– 10 times higher than the wear resistance of the untreated surface.
YURCHENCO, E.; Gheorghe GHILEȚCHII; Sergiu VATAVU; Vladimir PETRENCO; Diana HAREA; C. BUBULINCĂ și Alexandr DIKUSAR. Composition, Structure, and Wear Resistance of Surface Nanostructures Obtained by Electric Spark Alloying of 65G Steel. Surface Engineering and Applied Electrochemistry, 2024, vol. 60, pp. 194-203. ISSN 1068-3755.
Keywords: electric spark alloying; nanocrystalline materials; tribology; wear resistance; 65G steel; hard alloy; carbides